2014
DOI: 10.1089/fpd.2013.1706
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Campylobacter spp. from 40 Dairy Cattle Herds in Quebec, Canada

Abstract: Dairy cattle are considered a Campylobacter reservoir in the epidemiology of campylobacteriosis. Currently, very little data on the prevalence of Campylobacter in dairy herds are available in the Province of Quebec, Canada. The objectives of this study were to evaluate the prevalence of Campylobacter associated with management practices in 40 dairy cattle herds as well as to characterize the bacterial genetic diversity. Fecal samples from 797 lactating cows of 40 dairy farms, water provided to animals, milk fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…Among all the Campylobacter species detected in our study (27 classified species and 12 unclassified species), the nonthermotolerant C. hyointestinalis was the second most abundant and the third most prevalent Campylobacter species in the children stools. C. hyointestinalis was previously isolated from numerous livestock species such as swine (43), cattle (43)(44)(45)(46)(47)(48), sheep (43). However, its implication in human diseases is rare and sporadic (49)(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all the Campylobacter species detected in our study (27 classified species and 12 unclassified species), the nonthermotolerant C. hyointestinalis was the second most abundant and the third most prevalent Campylobacter species in the children stools. C. hyointestinalis was previously isolated from numerous livestock species such as swine (43), cattle (43)(44)(45)(46)(47)(48), sheep (43). However, its implication in human diseases is rare and sporadic (49)(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…However, its implication in human diseases is rare and sporadic (49)(50)(51)(52)(53). C. hyointestinalis has also been reported in developed countries, more precisely in feces collected from dairy farms in Canada (19.3%), in Finland (10.8%) and from dairy goat farms in New Zealand (2%), and in 3.2% milk samples collected from dairy farms in Italy (45,47,48,54). C. hyointestinalis, as well as, other Campylobacter species were also isolated from wild boar in Japan and dogs in Canada (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous studies in Canada, we found that the prevalence of Campylobacter spp. was highest in swine followed by beef cattle and dairy cattle (Inglis et al., ; Varela et al., ; Guévremont et al., ). Specifically, we found that there were significantly greater odds of isolating Campylobacter from swine samples compared to both dairy and beef cattle samples.…”
Section: Discussionmentioning
confidence: 99%
“…(reviewed in Humphrey et al 2007;Taboada et al 2013). The methods that are most widely used in Canada include (i) PFGE (e.g., Steele et al 1998;Nadeau et al 2002;Clark et al 2003;Guévremont et al 2004Guévremont et al , 2014, (ii) characterization of the flagellin locus through restriction fragment length polymorphism (fla RFLP) or DNA sequencing of the short variable region (fla SVR) (e.g., Clark et al 2005Clark et al , 2012Guévremont et al 2014), (iii) MLST (e.g., Clark et al 2005Clark et al , 2012, and (iv) CGF (Taboada et al , 2013Deckert et al 2014). Heat-stable serotyping and fla RFLP typing (Clark et al 2003), and Oxford MLST or fla SVR sequencing methods (Clark et al 2005) helped to identify the Campylobacter spp.…”
Section: Typing Methodsmentioning
confidence: 99%